Learning Innovation: Training on Video-Based Learning Media Development with Flipped Learning Model for Teachers of SMAN 2 Madapangga - Oya, Abas; Nurfidah, Nurfidah; Arwan, Arwan; Fauzi, Azra (STKI Harapan Bima, 2025)
This training initiative aims to enhance the teaching skills of educators at SMAN 2 Madapangga by introducing innovative video-based learning methods and incorporating the Flipped Learning model into their teaching practices. This program addresses the urgent need for user-friendly, technologically advanced teaching approaches in response to the rapidly evolving technological landscape. The training focuses on developing learning videos and video-recorded assignments, providing educators with practical skills in creating engaging and effective educational content. The methodology provides intensive training sessions, tool demonstrations, and personalized mentoring. The training is designed to equip educators with the necessary skills to effectively create, integrate, and assess video-based learning media. Results indicate successful implementation, with participants demonstrating a deep understanding of video creation concepts. Learning videos produced by participants received positive responses, improving students' engagement and understanding. Evaluation results highlight the effectiveness of the training, with suggestions for future improvements. In conclusion, this training program contributes to developing innovative teaching methods and fostering a dynamic and technology-enhanced learning environment for educators and students at SMAN 2 Madapangga. Future recommendations include advanced training, collaborative initiatives, regular evaluations, and exploration of additional technologies for an enriched learning experience.